Species Inventory and Potential of Gastropods at Tongga Beach, Mboeain Village, West Rote District, Rote Ndao Regency, Indonesia - Yanti Daud; Theodora Sarlotha Nirmala Manu; Fanny Iriany Ginzel (Jurnal Penelitian Pendidikan IPA, 2026)
Tongga Beach is one of the tourist destinations that is frequently visited by tourists as well as local residents from neighboring districts. In addition to serving as a recreational area, the surrounding community utilizes the beach as a source of livelihood by collecting fish, shellfish, and snails for consumption. The harvesting of these marine organisms is generally carried out during specific seasons, particularly the dry season, when low tide conditions make it easier for residents to collect shellfish, snails, and other marine organisms for personal consumption or commercial purposes. This study aimed to identify the species and potential uses of gastropods found at Tongga Beach, Mboeain Village, West Rote District, Rote Ndao Regency. The research was conducted from October to December 2024 using the line transect method. A total of 17 gastropod species were identified, belonging to 6 orders, 9 families, and 13 genera. Three gastropod species were utilized by the local community as food sources, namely Nerita picea, Canarium olydium, and Canarium urceus. In addition, 14 gastropod species were utilized as ornamental materials, including Cerithium nodulosum, Rhinoclavis vertagus, Clypeomorus bifasciata, Nerita plicata, Nerita tessellata, Conomurex luhuanus, Conus shikamai, Conus ebraeus, Vexillum dactylus, Strigatella retusa, Nassarius vibex, Crassispira quadrifasciata, Cymbiola rossiniana, and Helicigona faueri